MAIN FORMATION FACTORS OF GROUNDWATER CONTAMINATION FIELD UNDER THE INFLUENCEOF METALLURGICAL PRODUCTION (ON THE EXAMPLE OF DNIEPER METALLURGICAL PLANT) - Dolin, V.; Yakovlev, E.; Shcherbak, O.; Meshcheryakov, S.; Pampukha, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Purpose. Exploring the chemical composition of groundwater of natural and technogenic aquifer, formed within the area of metallurgical production of the Dnieper metallurgical plant. Objectives of the research: to identify the main pollutants of groundwater; establish the spatial structure of the field of pollution; classify the industrial site in terms of the environmental load of the main pollutants; estimate the migration properties of chemical elements in groundwater. Design/methodology/approach. Conceptual provision of research methodology was based on the role of the upper zone of the geological media (unsaturated zone or zone of aeration) as the main "accumulating depot" for the majority of anthropogenic emissions into the air, surface water, groundwater and terrain. The study was carried out on the laboratory results of water samples, slag and sludge. Findings. Thermal and chemical contamination, and abnormally high content of suspended solids in groundwater were detected and mapped within the investigated site of aquifer. Groundwater contamination by organic compounds (phenols, petroleum products) is the most acute problem. The study tested, as a result of technogenic activity of metallurgical production, the redox and the acid-alkaline conditions of unsaturated zone changed, which affects its barrier (protective) properties, decreasing the intensity of water migration of iron, manganese and zinc, with increased migration capacity of aluminum, lead and cadmium. Practical value/implications. As a result of research, it was established the overall state of the groundwater at the industrial site can be described as "relatively satisfactory environmental situation". Metallurgical production impacted on groundwater quality locally, particularly within the radial sedimentation tanks, sludge cards, coolers and other industrial units within unsaturated zone of geological media.